Risk factors related to dystocia in primiparous women at the Hospital General Dr. Napoleón Dávila Córdova - Véliz, Yandry M.; Marrero, Dadier; Navas, Valeria S. (Revista Gregoriana de Ciencias de la Salud, 2024)
Dystocia is a term that means laborious, difficult, and painful labor. They are alterations that occur in the pelvic-genital canal (bone and soft tissues), the fetus and uterine contractility. A retrospective cross-sectional descriptive study was carried out with the aim of analyzing the risk factors related to dystocic delivery in primiparous pregnant women at the Dr. Napoleón Dávila Córdova General Hospital from December 2019 to December 2020. From a universe of 380 pregnant women Primiparous women in labor attended in the emergency service of the hospital that appeared diagnosed with dystocia during the study period, a simple random sampling of 133 medical records was carried out for 35%. Breech presentation, pelvic narrowing, uterine malformations, arterial hypertension, maternal height less than 140 cm, and labor of more than 20 hours were identified as non-modifiable risk factors. It is concluded that the factors that most affected the presentation of dystocia in nulliparous women were insufficient prenatal controls, overweight and obesity in pregnant women.